2008
DOI: 10.1016/j.clsr.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Impact Assessments: International experience as a basis for UK Guidance

Abstract: In July 2007, the UK Information Commissioner's Office commissioned a team of researchers, coordinated by Loughborough University, to conduct a study into Privacy Impact Assessments (PIAs). This was with a view to developing PIA guidance for the UK. The project resulted in two key deliverables: a study of the use of PIAs in other jurisdictions, identifying lessons to be learnt for the UK; and a handbook that can be used to guide organisations through the PIA process, taking into account the provisions of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was a cognitive evaluation to check the feasibility of the research that will lead to the next comprehensive privacy protection guideline that suits the Malaysian culture. The methods of investigation conducted were adjusted from UK's three main procedures (Warren et al, 2008); i. The analysis was referred to relevant legislation and policy -OECD Guidelines, PHIPA and HIPC.…”
Section: Methodsmentioning
confidence: 99%
“…It was a cognitive evaluation to check the feasibility of the research that will lead to the next comprehensive privacy protection guideline that suits the Malaysian culture. The methods of investigation conducted were adjusted from UK's three main procedures (Warren et al, 2008); i. The analysis was referred to relevant legislation and policy -OECD Guidelines, PHIPA and HIPC.…”
Section: Methodsmentioning
confidence: 99%
“…Stewart (1999) also conducted research to evaluate how to improve the implementation of PIAs, and concluded that they could become a powerful vehicle for effective regulation. Warren et al (2008) sought to understand how one country (the United Kingdom, in this case) could learn from the experience of other countries in its use of PIAs to be effective in protecting information privacy, when systems and technologies affect information sharing. A current effort is unfolding in North America with the activities of the AICPA in the United States and the CICA in Canada.…”
Section: What Safeguards Are Needed At a Societal Level?mentioning
confidence: 99%
“…Privacy impact assessment (PIA) refers to a systematic assessment which can be incorporated in decision-making in privacy management [40]. Certain guidelines have been developed and released by organizations cross different countries [10,9,11].In a PIA template, each privacy risk can be evaluated by combining the quantities of impact and likelihood that it can cause [39].…”
Section: Privacy Assessmentmentioning
confidence: 99%